2004
DOI: 10.1183/09031936.04.00070503
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoidosis: social predictors of severity at presentation

Abstract: To determine relationships among social predictors and sarcoidosis severity at presentation, demographic characteristics, socioeconomic status, and barriers to care, A Case-Control Etiologic Study of Sarcoidosis (ACCESS) was set up.Patients self-reported themselves to be Black or White and were tissue-confirmed incident cases aged ol8-yrs-old (n=696) who had received uniform assessment procedures within one of 10 medical centres and were studied using standardised questionnaires and physical, radiographical, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 26 publications
1
62
0
3
Order By: Relevance
“…Thus, in general, patients with a high socioeconomic status reported a better health status. The same conclusion was drawn using data from A Case-Control Etiologic Study of Sarcoidosis (ACCESS) [61].…”
Section: Health Status In Sarcoidosismentioning
confidence: 53%
“…Thus, in general, patients with a high socioeconomic status reported a better health status. The same conclusion was drawn using data from A Case-Control Etiologic Study of Sarcoidosis (ACCESS) [61].…”
Section: Health Status In Sarcoidosismentioning
confidence: 53%
“…Older individuals were more likely to have severe disease by both measures. In conclusion, it was found that low income and other financial barriers to care are significantly associated with Sarcoidosis severity at presentation even after adjusting for demographic characteristics of race, sex, and age [56].…”
Section: Sarcoidosismentioning
confidence: 97%
“…To confirm the previous study Rabin et al [56] set out to determine sarcoidosis disease severity at first presentation. The results of the study showed that lower income, the absence of private or Medicare health insurance were associ-www.journals.viamedica.pl ↓ SES is associated more severe disease at presentation SES -socioeconomic status ated with sarcoidosis severity at presentation, as were race, sex, and age.…”
Section: Sarcoidosismentioning
confidence: 99%
“…Multiple studies show that sarcoidosis tends to be more severe in black patients, whereas, white patients are more likely to have spontaneous resolution. [23,24] Japanese patients have a higher prevalence of cardiac and ocular disease than Western populations. [8] Last, lower socioeconomic status has been associated with more severe disease and new organ involvement.…”
Section: Morbiditymentioning
confidence: 99%